The Role of Sustained Photoprotective Non-photochemical Quenching in Low Temperature and High Light Acclimation in the Bloom-Forming Arctic Diatom Thalassiosira gravida - Lacour, Thomas; Larivière, Jade; Ferland, Joannie; Bruyant, Flavienne; Lavaud, Johann; Babin, Marcel (Frontiers in Marine Science, 2018)
Thalassiosira gravida is a major Arctic diatom responsible for the under-ice spring bloom. We investigated T. gravida physiological plasticity growing it at two temperatures (0°C and 5°C) and under different light intensities typically found in its natural environment. T. gravida showed remarkable thermal- and photo-acclimatory plasticity including: low light saturation parameter for growth (KE) and photosynthesis (EK), low μmax but relatively high Chl a/C, low C/N and decreasing light-saturated carbon fixation rate (PCm) with increasing growth irradiance. T. gravida also showed remarkable photoprotective features, namely a strong sustained non photochemical quenching (NPQs, hour kinetics relaxation) supported by a high amount of xanthophyll cycle pigments. T. gravida growth remained possible under a wide range of irradiances but photosynthetic plasticity was higher at moderately low light (up to 50 µmol photon m-2 s-1), nevertheless corresponding to the mean in situ conditions under which it predominates, i.e. underneath the spring thin-ice punctuated with melting ponds. The potential role of NPQs in the photophysiological plasticity of T. gravida is discussed.